Microstructures, properties, and applications of laser sintered 17-4PH stainless steel - GÜLSOY, HAMİT ÖZKAN (WILEY, 2019)
The effects of hot isostatic pressing (HIP) on the densification, mechanical properties, and microstructures of laser-powder bed fusion (L-PBF) 17-4 PH stainless steel parts were studied using gas- and water-atomized powders. The % theoretical density, ultimate tensile strength, yield strength, elongation, and hardness of as-printed and HIP-ed L-PBF parts were sensitive to energy density and starting powder shape, size, and type. At low-energy densities of 64 and 80J/mm(3), densification was significant for water-atomized L-PBF parts when subjected to HIP treatment and density increased from 90% to 97%. For all the energy densities, the gas-atomized L-PBF parts after the HIP treatment showed significantly higher tensile strength, yield strength, and hardness when compared to water-atomized L-PBF parts properties. At low-energy densities of 64 and 80J/mm(3), long columnar grains in the as-printed L-PBF parts did not change significantly after the HIP treatment whereas the columnar grains present in as-printed gas-atomized L-PBF parts completely disappeared when subjected to HIP treatment. However, at high-energy densities of 84 and 104J/mm(3), the columnar grains in as-printed L-PBF gas- and water-atomized L-PBF parts were changed to equiaxed grains and showed a higher level of homogenization when subjected to HIP treatment. This variation in grains and grain size had significantly affected the yield strength and elongation of HIP-treated gas- and water-atomized L-PBF parts.
Keywords: grain size; hot isostatic pressing; mechanical properties; microstructure; MECHANICAL-PROPERTIES; PROCESSING CONDITIONS; POWDER; DENSIFICATION; PARTS; BEHAVIOR; COMPONENTS; POROSITY; FUSION; GAS